2008
DOI: 10.4257/oeco.2008.1202.07
|View full text |Cite
|
Sign up to set email alerts
|

Benthic marine algae of the coral reefs of Brazil: a literature review

Abstract: In Brazil, algae in coral reef environments can be found from Maranhão to Bahia State and there are today around 700 taxa, of which 78% are found on reef formations. The Rhodophyta are among the most common taxa found. Corallinales are the least studied group, in spite of their role in the formation and maintenance of Brazilian coral reefs. The species richness of algae on coral reefs is low in comparison with other coastal habitats, but there is an abundance of turf and fleshy macroalgae on certain parts of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 70 publications
(73 reference statements)
0
17
1
3
Order By: Relevance
“…In one of the few studies on rhodolith-associated benthic communities elsewhere in Brazil, Riul et al (2009) identified 67 seaweed species in a rhodolith bed between 10 and 20 m depth from the northeastern coast. Figueiredo et al (2008) recently summarized the benthic marine algae of Brazilian coral reefs, and the highest richness so far recorded in Brazil is less than that found in the present study, with species richness ranging from 51 taxa in the protected Recife de Fora Marine Reserve (Bahia State) to 122 taxa in Fernando de Noronha National Park (Pernambuco State). An important feature of some of the Brazilian coral reefs is that they are chiefly composed of nongeniculate coralline algae (Kikuchi and Leão 1997).…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…In one of the few studies on rhodolith-associated benthic communities elsewhere in Brazil, Riul et al (2009) identified 67 seaweed species in a rhodolith bed between 10 and 20 m depth from the northeastern coast. Figueiredo et al (2008) recently summarized the benthic marine algae of Brazilian coral reefs, and the highest richness so far recorded in Brazil is less than that found in the present study, with species richness ranging from 51 taxa in the protected Recife de Fora Marine Reserve (Bahia State) to 122 taxa in Fernando de Noronha National Park (Pernambuco State). An important feature of some of the Brazilian coral reefs is that they are chiefly composed of nongeniculate coralline algae (Kikuchi and Leão 1997).…”
Section: Discussioncontrasting
confidence: 46%
“…En uno de los pocos estudios realizados sobre las comunidades bénticas asociadas con rodolitos en Brasil, Riul et al (2009) identificaron 67 especies de algas en un manto rodolítico entre 10 y 20 m de profundidad en la costa nororiental. Figueiredo et al (2008) recientemente resumieron las algas marinas bénticas de arrecifes coralinos de Brasil, y la mayor riqueza registrada a la fecha es menor que la encontrada en el presente estudio, con la riqueza de especies oscilando entre 51 taxones en la Parque Marino Recife de Fora (estado de Bahía) y 122 taxones en el Parque Nacional Fernando de Noronha (estado de Pernambuco). Una característica importante de algunos arrecifes coralinos brasileños es que se componen principalmente de algas coralinas no geniculadas (Kikuchi y Leão 1997).…”
Section: Discussionunclassified
“…Species ascribed to the genus Porolithon Foslie have been highlighted as being particularly important (Lee 1967, Adey 1978, Littler 1973, Littler & Doty 1975, Adey et al 1982, Gherardi & Bosence 1999, Littler & Littler 2000, Villas Bôas et al 2005, Figueiredo et al 2008. Notably, Porolithon onkodes (Heydrich) Foslie emend.…”
Section: Introductionmentioning
confidence: 99%
“…The success of this colonization depends on the growth strategy of each species in the competition for space (Paine 1984;Steneck et al 1991;) in relation to physical conditions (Littler and Littler 1984;Kendrick 1991;Steneck and Dethier 1994) or biological disturbances (Paine 1984;Steneck et al 1991). Figueiredo (1997) showed that CCA in the southwest Atlantic have a similar degree of cover on wave-exposed offshore reefs after 3-5 months of colonization, in shallow zones dominated by Porolithon pachydermum (Foslie) Foslie and Lithophyllum congestum (Foslie) Foslie (Figueiredo and Steneck 2002;Figueiredo 2006;Figueiredo et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Species composition and cover of CCA and corals on the emergent banks of Brazilian reefs have been observed to change markedly at different intervals (Leão and Kikuchi 2005;Figueiredo et al 2008). Turf algae, fleshy algae Communicated by I. Bartsch.…”
Section: Introductionmentioning
confidence: 99%